Pelatihan Penggunaan ERISE sebagai Media Pembelajaran Kearsipan Elektronik bagi Guru SMK Otomatisasi dan Tata Kelola Perkantoran Di Daerah Istimewa Yogyakarta - Yuliansah, Yuliansah; Sutirman, Sutirman; Dwihartanti, Muslikhah; Kistiananingsih, Isti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Electronic record management is one of the main competencies of OTKP SMK graduates. Therefore, teachers in SMK OTKP must have knowledge and skills in electronic record management and be able to use appropriate instructional media. This community service aims to 1) increase the knowledge of OTKP VHS teachers in electronic record management, and 2) improve the skills of OTKP VHS teachers in electronic record management material. Community service activities used a variety of methods, including lectures, demonstrations, discussions, and practice. The results of the community service activities that have been achieved are as follows: 1) The knowledge of OTKP VHS teachers in electronic record management was increased, and 2) The skills of OTKP VHS teachers in electronic record management material were improved. All participants in the training understood and practiced electronic record management well.